2013
DOI: 10.1111/all.12174
|View full text |Cite
|
Sign up to set email alerts
|

The history of the idea of allergy

Abstract: About 100 years ago, a young paediatrician understood that the function of the immune system should be rationalized not in terms of exemption of disease but in terms of change of reactivity. He coined a new word to represent such an idea: 'allergy': the first contact of the immune system with an antigen changes the reactivity of the individual; on the second and subsequent contacts, this change (or allergy) can induce a spectrum of responses from protective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 29 publications
1
26
0
2
Order By: Relevance
“…6 A review and update of hypersensitivity (allergy) concepts was presented by Kay 4 and reviewed by Igea. 7 The allergy conditions seen in pediatric allergy clinics were defined by a Nomenclature Committee for dissemination by the European Academy of Allergology and Clinical Immunology, World Allergy Organization, and American Academy of Allergy, Asthma, and Clinical Immunology. 8 The original Gell and Coombs 2 hypersensitivity reactions, with a modification by Rajan 6 are outlined in Table 1.…”
Section: Hypersensitivity Terminology: Historical and Currentmentioning
confidence: 99%
“…6 A review and update of hypersensitivity (allergy) concepts was presented by Kay 4 and reviewed by Igea. 7 The allergy conditions seen in pediatric allergy clinics were defined by a Nomenclature Committee for dissemination by the European Academy of Allergology and Clinical Immunology, World Allergy Organization, and American Academy of Allergy, Asthma, and Clinical Immunology. 8 The original Gell and Coombs 2 hypersensitivity reactions, with a modification by Rajan 6 are outlined in Table 1.…”
Section: Hypersensitivity Terminology: Historical and Currentmentioning
confidence: 99%
“…Von Pirquet observed that changes in reactivity occurred on subsequent exposures to an antigen. In some instances, re-exposure resulted in diminished reactivity whereas in others reactivity increased (Igea, 2013). A major advance in the understanding of food allergy occurred in 1921, when Prausnitz and Kustner determined that hypersensitivity to an antigen could be passively transferred with serum from one individual—namely, Kustner, who was allergic to fish—to another—namely, Prausnitz, who was not allergic to fish—by intradermal injection.…”
Section: Why Does Allergy Exist?mentioning
confidence: 99%
“…This definition indicates a change in the sensitivity of the organism to substances with which the organism previously contacted. [1] At first, the allergic reactivity was connected to the development of inflammatory reaction in the point of allergen influence. Later, with the data discovery for histohematic barriers role, the new views on the allergy development mechanism shave formed.…”
Section: Introductionmentioning
confidence: 99%